Efforts to improve Sales Volume at PT. Pratamabina Meditama - Amril; Rianto (Jurnal Manajemen Bisnis Eka Prasetya Penelitian Ilmu Manajemen, 2023)
This study aims to determine the effect of the Work Environment on Sales Volume at PT. Pratamabina Meditama, knowing the effect of Service Quality on Sales Volume at PT. Pratamabina Meditama, knowing the effect of Work Environment and Service Quality on Sales Volume at PT. Pratamabina Meditama. The population in this study were all consumers who used the company’s services during the 2020 period as many as 7,101 consumers. By using the Slovin formula with an error rate of 10%, the number of samples obtained is 99 respondents. The results showed that the work environment and service quality partially had a positive and significant effect on the sales volume of consumers at PT. Pratamabina Meditama. The results showed that the work environment and service quality simultaneously had a positive and significant effect on the sales volume of consumers at PT. Pratamabina Meditama. The results of this study are supported by the value of R square (R2), which means that the work environment and service quality have an influence on sales volume. While the rest is influenced by other factors that come from outside this research model such as product quality, employee performance, design, satisfaction, loyalty and various other variables.